Work-Family Conflict of Career Woman with Family Well-Being in the City of Kupang - Andhrea Mesakh; Serlie K. A Littik; Yeni Damayanti (Universitas Nusa Cendana, 2023)
Along with the times, it is not only men who make a living but women also have a role in earning a living for the family. This causes problems in carrying out their roles as mothers and career women, thus making one another's roles unable to be carried out correctly and fairly. This study aims to explain the relationship between work-family conflict between career women who work with family well-being in Kupang City. The subjects of this study amounted to 200 participants with the criteria of career woman and career man, have school-age children, live with husband/wife and children, and the amount of time work reaches 45 hours/week or five days/week. The research method uses a descriptive quantitative approach using an ordinal scale. The measuring instrument used is the harmony scale based on the adaptation of the first study developed in Hong Kong by Moonly M.C. Wong, et al in 2022 and the work-family conflict scale using the Work-Family Conflict Scale (WAFCS) in 2014. The results of the study found that there was a negative relationship between work-family conflict and family well-being. The higher the work-family conflict, the lower the family well-being and vice versa. The tests showed no difference in the work-family conflict between men and women in carrying out their roles at work and in the family.